Breakdown in Nanofluids: A Short Review on Experimental Results and Related Mechanisms - Danikas, M. (Engineering, Technology & Applied Science Research, 2018)
Nanofluids seem to gradualy become an alternative to traditional insulating liquids, such as transformer oil. In this paper, a short review of experimental results as well as of possible breakdown mechanisms and of some of the factors affecting the breakdown strength of the said fluids is conducted. Most of the reports suggest that the addition of nanoparticles in insulating liquids improves the breakdown strength. However, some reports that contradict the above are also to be found. In view of this, an outline of future research is discussed. This review does not encompass all possible effects, parameters and factors affecting nanofluids but it is solely concerned with breakdown strength.